Intentional incisions on Neolithic Obsidian arrowheads from Central Anatolia: A techno-functional and iconographic approach - Alice Vinet; Denis Guilbeau (PLoS ONE, 2026)
Incised obsidian arrowheads form a rare and geographically restricted artifact class, known exclusively from Neolithic Central Anatolia between the late 8th and 7th millennia BCE. These artifacts, marked by deliberate incisions, have been variously interpreted as symbolic or identity-related. This study presents a comprehensive techno-functional and iconographic analysis of eleven newly identified specimens from Tepecik-Çiftlik (Cappadocia, Türkiye), adding to the regional corpus of 43 known examples. The incised arrowheads were found in dwelling sites, a chipped stone workshop, and during surveys.Provenance analysis by macroscopic characterization confirms their production from local Cappadocian obsidian sources (Göllüdağ, Nenezi Dağ). The incisions are highly variable, and show no correlation with raw material, chaîne opératoire , typology, or use-wear. Incisions were executed both before and after final retouching, suggesting no fixed production stage. Comparative analysis reveals parallels between sites, indicating a possible shared but flexible iconographic repertoire. The rarity of these artifacts, their relation to domestic contexts, and their absence beyond Central Anatolia point to the hypothesis of a shared cultural practice. The analysis of these incised arrowheads, along with the limited archaeological and ethnographic comparisons available, calls for a cautious interpretation. While they have been suggested as personal or collective markers (e.g., hunters’ marks), this hypothesis requires further evidence. The expanded dataset from Tepecik-Çiftlik refines the understanding of this peculiar practice, highlighting its persistence despite broader cultural change.